Pemikiran etnopuitika dalam pagelaran wayang Jawa - Suwarna, Suwarna (Kejawen, 2025)
Wayang has a extraordinary power in hold out or survival for one thousand years. The wayang’s power that should be researched. One of the wayang’s power is aesthetics, concist of: the universality of the texts and the art of sounding the narrative texts. The etnopoetics approach of wayang as javanese culture need (1) the wayang showing or staging, (2) the universality of the texts and the art of sounding the narrative texts; both of monoaesthetics or multiaesthetics,(3) frame of local culture, and (4) the knowledge of wayang arts.